2004
DOI: 10.1557/proc-851-nn8.7
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Polymers based on Poly(m -carboranyl-siloxane) Elastomers

Abstract: Poly(m-carboranyl-siloxane) elastomers containing a mixture of di-methyl-and methyl(phenyl)-silyl units were synthesised using the Ferric Chloride catalysed condensation reaction between di-chloro-di-organosilane and 1,7-bis(di-methyl(methoxy)silyl)-m-carborane. These prepared polymers were aged either by heating in air at elevated temperature or by γirradiation from a 60 Co source. Multinuclear ( 1 H, 13 C and 11 B) solid and solution state nuclear magnetic resonance was used to evaluate degradation. γ-irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The thermo‐oxidative stability of the polymers could be greatly improved by chemical incorporation of icosahedral caboranes. Carborane‐containing polymers, such as polyetherketones, polysilanes and polysiloxanes have been prepared as advanced materials with unique thermostabilities . However, to the best of our knowledge, no study of polybenzoxazines based on icosahedral caboranes has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The thermo‐oxidative stability of the polymers could be greatly improved by chemical incorporation of icosahedral caboranes. Carborane‐containing polymers, such as polyetherketones, polysilanes and polysiloxanes have been prepared as advanced materials with unique thermostabilities . However, to the best of our knowledge, no study of polybenzoxazines based on icosahedral caboranes has been reported.…”
Section: Introductionmentioning
confidence: 99%